Niche partitioning by functional groups of tree species in a subtropical forest Partição de nicho por grupos funcionais de espécies arbóreas em uma floresta subtropical - Souza K.* (2017)
This study aimed to investigate functional attributes of tree species along different topographic position, in a forest located in Upper Uruguay region, in Santa Catarina. The wood density (WD), potential height (Hmax), leaf area (LA), specific leaf area (SLA), leaves renovation regime, regeneration and dispersal guilds were determined for the 20 most abundant species in the sampled area. The functional structure was evaluated through a community weight matrix (CWM) of traits values for each sampling unit. Mean values of elevation, declivity and curvature were extracted for each sampling unit, from a Terrain Digital Model in a resolution of 1 m. The data was analyzed through linear correlations, Principal Coordinates Analysis (PCoA), Principal Components Analysis (PCA) and linear simple model. The results indicated significant and negative correlation between Hmax x LA and Hmax x SLA. The topographic gradient significantly influenced the functional structure of tree component. It is concluded that the occupation of different positions along the topographic gradient and the forest vertical profile by tree species were mediated by different ecological strategies.